The Role of Farmers in Developing the Existence of Madrasah Diniyah Takmiliyah Wustho Al-Munawaroh - Sulistiyawati, Sulistiyawati; Amirudin, Noor (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
Community participation, both material and moral, is very important in efforts to develop the Diniyah takmiliyah Wustho madrasah. This research aims to analyze the role of the farming community in the development of Madrasah Diniyah Takmiliyah wustho in Timbuan Hamlet, Tambakmenjangan Village, Sarirejo District, Lamongan Regency. The subjects of this research are people who work as farmers in the hamlet who are in the development and existence of activities at Madrasah Diniyah Takmiliyah Wustho. This research method is a qualitative approach. Data collection techniques use participant observation, in-depth interviews, and documentation. The research results show that the farming community has an important role in the development of Madrasah Diniyah Takmiliyah Wustho. This is proven by the high enthusiasm of the Timbuan Hamlet farming community to contribute to the development and existence of activities at the madrasah. This enthusiasm is based on several factors, namely the opinion that the Diniyah takmiliyah wustho madrasah is an educational institution with complete knowledge because it teaches general knowledge and religious knowledge, the integration of learning Islamic religious knowledge into life, the view that rural communities still prioritize morals over knowledge, and the approach madrasas through regular monthly meetings. very affecting. From this it can be concluded that community relations in the world of education is a unique management function and supports the development and maintenance of community members, both communication and between organizations